2005
DOI: 10.1093/pci/pci001
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Rhizobium and Nitric Oxide Induce Gene Expression of Non-symbiotic Hemoglobin in Lotus japonicus

Abstract: We characterized the expression profiles of LjHb1 and LjHb2, non-symbiotic hemoglobin (non-sym-Hb) genes of Lotus japonicus. Although LjHb1 and LjHb2 showed 77% homology in their cDNA sequences, LjHb2 is located in a unique position in the phylogenetic tree of plant Hbs. The 5'-upstream regions of both genes contain the motif AAAGGG at a position similar to that in promoters of other non-sym-Hb genes. Expression profiles obtained by using quantitative RT-PCR showed that LjHb1 and LjHb2 were expressed in all ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
112
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 34 publications
3
112
1
2
Order By: Relevance
“…The role of NO is much more obscure in symbiotic systems. On one hand, the transient NO generation observed in Lotus japonicus roots at 4 h after Mesorhizobium loti inoculation paralleled the enhanced expression of a nonsymbiotic hemoglobin gene LjHb1, possibly involved in NO detoxification (Shimoda et al 2005;Nagata et al 2008). These authors suggested the quick generation of NO to be the signal triggering NO-mediated defense responses in the host plant.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The role of NO is much more obscure in symbiotic systems. On one hand, the transient NO generation observed in Lotus japonicus roots at 4 h after Mesorhizobium loti inoculation paralleled the enhanced expression of a nonsymbiotic hemoglobin gene LjHb1, possibly involved in NO detoxification (Shimoda et al 2005;Nagata et al 2008). These authors suggested the quick generation of NO to be the signal triggering NO-mediated defense responses in the host plant.…”
Section: Discussionmentioning
confidence: 94%
“…This suggests that early NO production is an AM-specific component of the plant response within the "common SYM pathway." Notably, Shimoda et al (2005) described NO production in L. japonicus roots 4 h after rhizobium inoculation; however, they did not test the effect of purified Nod factor and rather proposed rhizobial LPS as the candidate inducers of NO production (Nagata et al 2009). It will be interesting to evaluate whether the LCO recently identified as part of the fungal exudates of G. intraradices (Maillet et al 2011) are responsible for the induction of NO production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baudouin et al (2006) have shown that NO is produced in rhizobia-containing cells of nodules of the legume Medicago truncatula. Consistent with their function of lowering internal NO levels, class I hemoglobins are formed in the infected cells of Lotus japonicus nodules (Uchiumi et al 2002;Shimoda et al 2005). The reconstitution of class I Hb after NO scavenging requires the oxidation of ascorbate ( Figure 1).…”
Section: Nodule Oxygen Protection Mechanisms Lead To Oxidative Stressmentioning
confidence: 75%
“…170, 1052Sci. 170, -1058 Gallardo, K., Firnhaber, C., Zuber, H., Hericher, D., Belghazi, M., Henry, C., Küster,8 H., Thompson, R., 2007. A combined proteome and transcriptome analysis of 9…”
mentioning
confidence: 99%